The Msn2 Transcription Factor Regulates Acaricidal Virulence in the Fungal Pathogen Beauveria bassiana - Muniz, Elen R.; Ribeiro-Silva, Cárita S.; Arruda, Walquíria; Keyhani, Nemat O.; Fernandes, Éverton K. K. (Frontiers in Cellular and Infection Microbiology, 2021)
Beauveria bassiana holds promise as a feasible biological control agent for tick control. The B. bassiana stress response transcription factor Msn2 is known to contribute to fungal growth, conidiogenesis, stress-response and virulence towards insects; however, little is known concerning whether Msn2 is involved in infection across Arthropoda classes. We evaluated the effects of Msn2 on B. bassiana virulence against Rhipicephalus microplus (Acari, Ixodidae) using wild type, targeted gene knockout (ΔBbmsn2) and complemented mutant (ΔBbmsn2/Bbmsn2) strains. Reproductive parameters of R. microplus engorged females treated topically or by intra-hemocoel injection of conidial suspensions were assessed. Treated cuticles of engorged females were analyzed by microscopy, and proteolytic activity of B. bassiana on cuticles was assessed. Topically treated engorged females showed high mean larval hatching (>84 %) in control and ΔBbmsn2 treatments, whereas treatment with the wild type or ΔBbmsn2/Bbmsn2 strains resulted in significantly decreased (lowered egg viability) larval hatching. Percent control of R. microplus topically treated with ΔBbmsn2 was lower than in the groups treated with wild type (56.1 %) or ΔBbmsn2/Bbmsn2 strains. However, R. microplus injected with high doses of wild type or mutant strains (106 conidia/tick) died before laying eggs (~48h after treatment). SEM analyses of B. bassiana infection showed similar conidial germination and formation of pseudo-appressoria on tick cuticle. Histological sections of ticks treated with the wild type or ΔBbmsn2/Bbmsn2 strains showed fungal penetration through the cuticle, and into the tick interior. Hyphae of ΔBbmsn2, however, did not appear to penetrate or breach the tick exocuticle 120 h after treatment. Protease activity was lower on tick cuticles treated with ΔBbmsn2 than those treated with the wild type or ΔBbmsn2/Bbmsn2 strains. These data show that loss of the Msn2 transcription factor reduced B. bassiana virulence against R. microplus, but did not interfere with conidial germination, appressoria formation or sporulation on tick cadavers, and plays only a minimal role once the cuticle is breached. Our results indicate that the BbMsn2 transcription factor acts mainly during the fungal penetration process and that decreased protease production may be one mechanism that contributes to the inability of the mutant strain to breach the tick cuticle.